PERBEDAAN INDEKS MASSA TUBUH TERHADAP CITRA TUBUH PADA REMAJA PEREMPUAN - Utami, Dewa Ayu Diah Budi; Juniartha, I Gusti Ngurah; Suindrayasa, I Made (Coping: Community of Publishing in Nursing, 2021)
Adolescent girls have different perceptions of their body mass index and body image. Body mass index can affect an adolescent girl's body image. Body image is the way adolescent girls perceive or think about their bodies. Adolescent girls generally tend to experience body image dissatisfaction because of their body shape. The differences in body mass index caused by adolescent girls' perceptions will be varied. The purpose of this study was to analyze the comparison of body mass index towards body image among adolescent girls of grade 10th MIPA in SMAN 1 Gianyar. This is a non-experimental comparative descriptive study using a cross-sectional design conducted in SMAN 1 Gianyar. The research sample consisted of 137 adolescent girls obtained by the total sampling technique. The research instruments used were a body image questionnaire, microtoise, and weight scale. The data were analyzed by the Kruskal-Wallis test. The analysis showed that there was a difference significant in body mass index of body image among adolescent girls in grade 10th. This research can be a guideline for school and primary health canter to more consent in adolescent girls psychologically. Adolescent girls are expected to improve their body image with more confidence so it’s can avoid psychological problems.